2017
DOI: 10.1128/iai.00814-16
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Toll-Like Receptor 9, Myeloid Cells, and Deubiquitinase A20 in Periodontal Inflammation

Abstract: Toll-like receptor 9 (TLR9)-deficient (TLR9 Ϫ/Ϫ ) mice are resistant to periodontitis, a disease characterized by a dysbiotic microbiota and deregulated immune response and resulting in tooth loss and various systemic conditions. However, the mechanisms and biological pathways by which TLR9 instigates periodontal inflammation are yet to be identified. In a ligature-induced model of periodontitis, we demonstrate that TLR9 Ϫ/Ϫ mice exhibited significantly less alveolar bone loss than their wild-type (WT) counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 43 publications
4
60
0
2
Order By: Relevance
“…The genes encoding important molecules involved in periodontal inflammation identified in previously published articles include matrix metallopeptidases including MMP1 , MMP2 , MMP3 , MMP8 , MMP9 and MMP13 and tissue inhibitors of metalloproteinases including TIMP1 , TIMP3 and TIMP4 ; various interleukin (IL) families including IL1 β, IL2 , IL4 , IL6 , IL8 , IL10 , IL11 , IL 12 , IL17A , IL17F , IL18 , IL21 , IL23 and IL35 ; the pentraxin family including C‐reactive protein/pentraxin 1 ( CRP / PTX1 ) and pentraxin 3 ( PTX3 ); the TNF superfamily TNF‐ α and the receptor activator of the NFκB ligand/TNF superfamily member 11 ( RANKL / TNFSF11 ); the TNF receptor superfamily osteoprotegerin/TNF receptor superfamily member 11b ( OPG / TNFRSF11B ); the transforming growth factor (TGF) superfamily TGF β 1 ; the TLR family including TLR2 and TLR4 ; chemokines including C‐C motif chemokine ligands ( CCL2 , CCL3 , CCL5 , CCL19 , CCL20 ), C‐C motif chemokine receptor 4 ( CCR4 ) and C‐X‐C motif chemokine ligands ( CXCL6 , CXCL8 / IL8 ); suppressors of cytokine signalling including SOCS1 and SOCS3 ; interferon IFN‐ γ; transcription regulator T‐box 21 ( TBX21 ); NF κ B / NFKB1 ; TNF‐α‐induced protein 3 ( TNFAIP3 ); peptidylprolyl isomerase A/cyclophilin A ( PPIA / CypA ); and cyclooxygenase 2/prostaglandin‐endoperoxide synthase 2 ( COX2/PTGS2 ) . By combining the retrieval and computer algorithm prediction results, potential target genes related to periodontal inflammation were determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes encoding important molecules involved in periodontal inflammation identified in previously published articles include matrix metallopeptidases including MMP1 , MMP2 , MMP3 , MMP8 , MMP9 and MMP13 and tissue inhibitors of metalloproteinases including TIMP1 , TIMP3 and TIMP4 ; various interleukin (IL) families including IL1 β, IL2 , IL4 , IL6 , IL8 , IL10 , IL11 , IL 12 , IL17A , IL17F , IL18 , IL21 , IL23 and IL35 ; the pentraxin family including C‐reactive protein/pentraxin 1 ( CRP / PTX1 ) and pentraxin 3 ( PTX3 ); the TNF superfamily TNF‐ α and the receptor activator of the NFκB ligand/TNF superfamily member 11 ( RANKL / TNFSF11 ); the TNF receptor superfamily osteoprotegerin/TNF receptor superfamily member 11b ( OPG / TNFRSF11B ); the transforming growth factor (TGF) superfamily TGF β 1 ; the TLR family including TLR2 and TLR4 ; chemokines including C‐C motif chemokine ligands ( CCL2 , CCL3 , CCL5 , CCL19 , CCL20 ), C‐C motif chemokine receptor 4 ( CCR4 ) and C‐X‐C motif chemokine ligands ( CXCL6 , CXCL8 / IL8 ); suppressors of cytokine signalling including SOCS1 and SOCS3 ; interferon IFN‐ γ; transcription regulator T‐box 21 ( TBX21 ); NF κ B / NFKB1 ; TNF‐α‐induced protein 3 ( TNFAIP3 ); peptidylprolyl isomerase A/cyclophilin A ( PPIA / CypA ); and cyclooxygenase 2/prostaglandin‐endoperoxide synthase 2 ( COX2/PTGS2 ) . By combining the retrieval and computer algorithm prediction results, potential target genes related to periodontal inflammation were determined.…”
Section: Methodsmentioning
confidence: 99%
“…NFκB/NFKB1 36 ; TNFα-induced protein 3 (TNFAIP3) 37 ; peptidylprolyl isomerase A/cyclophilin A (PPIA/CypA) 38 ; and cyclooxygenase 2/prostaglandin-endoperoxide synthase 2 (COX2/PTGS2). 39 By combining the retrieval and computer algorithm prediction results, potential target genes related to periodontal inflammation were determined.…”
Section: Bioinformatic Analysis and Target Selectionmentioning
confidence: 99%
“…A20 is implicated as a key regulator of epithelial cell biology in a variety of tissues (13)(14)(15)(16)(17)(18)(19). Clinically, A20 protein is expressed in the gingival epithelium, but there are still no studies investigating its function in the gingival epithelial cells (20). In this study, through elaborate use of gain and loss of function assays, we identified A20 as one of the novel regulators of inflammatory and apoptotic responses in gingival keratinocytes.…”
Section: Introductionmentioning
confidence: 90%
“…Porphyromonas gingivalis (strain ATCC33277) was maintained in Brain Heart Infusion supplemented with 0.05% Yeast Extract, 5 g/mL Hermin, 0.5 g/mL Vitamin K and 0.1% cysteine. The culture was placed in anaerobic chambers at 37 • C. Bacteria were killed by heating at 80 • C for 10 min (20). Heat-killed bacteria were used for all experiments except for P. gingivalis induced apoptosis.…”
Section: Bacteria and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation